Avaliação da bexiga fetal através da ultra-sonografia tridimensional: reprodutibilidade da técnica rotacional - Peixoto Filho, Fernando Maia (2007)
Objective: The aim of this study was to investigate the inter- and intraobserver reliability in measuring the fetal bladder volume by 3D ultrasound (US) imaging using the Virtual Organ Computed-aided Analysis (VOCALTM) comparing the 15° and 30° rotation steps calculation. Methods: We analysed 240 measurements of FB volume performed in 30 low-risk patients with gestation ages ranging from 22 to 39 weeks by two independent observers blind to each other. All fetuses were examined and no ultrasound detectable malformation was found. The volume of each FB was measured twice by each observer using the VOCALTM technique. Distinct sets of 12 and 6 planes were obtained after sequential rotations of 15° and 30°, respectively. The internal contour of the fetal bladder was manually and carefully determined as to exclude adjacent structures from volume calculation. Wilcoxon signed-rank test was used to compare the paired samples in the cases of replication within and between observers. Spearman s rank correlation was used to study the relationship among angles. Bland and Altman s graphical approach was used to investigate the agreement between observers. Results: The 3D VOCALTM technique showed itself as highly reliable in our sample. No significant difference was found between the measurements of FB volume with the VOCALTM technique either by varying the steps of rotation or the observers. Conclusion: Good correlations were found for both observers in the use of rotation angles of 15° and 30°. Since a significantly faster evaluation was obtained by using the 30° rotation step it must be preferred to assess the FB volume.